Research methods in human resource management : investigating a business issue. - Anderson, Valerie (Principal lecturer); Fontinha, Rita (KoganPage, 2024)
Fully updated throughout, this fifth edition is essential reading for master's-level CIPD and non-CIPD students alike. Balancing theoretical frameworks and practical guidance, 'Research Methods in Human Resource Management' explains everything from the first stages of a HR research project from defining a hypothesis and planning the research process through to reviewing literature and documents, collecting and analysing both qualitative and quantitative data. There is also guidance on how to write up the research project with best practice sample literature reviews and write-ups included.